Mathematical modeling and mechanical characterization through process parameters optimization of AlMg-matrix SiCp reinforced composites produced by powder metallurgy route. (2021) - Zegeye, Dessalegn Bayu; Sinha, Devendra Kumar; Venkatesh, C.; Kumar, Anil; Jha, Pushkar
Abstract: Aluminum-magnesium (AlMg) alloys possess many uses in the current scenario for universal use specially in aerospace, automotive, and computer industries; due to the lightweight, good identified strengths, high recyclability, and low density . In this research paper, the high-performance lightweight AlMg-matrix with different weight percentages (wt.%) of SiC particles reinforcement, high strength materials is produced by powder metallurgy (PM) technique, using Taguchi L9 orthogonal array experimental design. Analysis of the effects of the PM process parameter on porosity, actual and relative density have been investigated with the "smaller is best" formula. The porosity, as well as the actual density for both the matrix and composite specimens have been calculated with the Archimedes' fundamental principles. The three basic processing variables in PM route, such as, pressure of compaction, sintering temperature, sintering duration and the SiC reinforcement in different wt.% were consider. The increment of SiC wt.% in the matrix results high hardness composite materials with good densification at best pressure of compaction, sintering temperature, and sintering duration. When the wt.% of SiC increases, less increment of porosity is observed for the fabricated AlMg/SiC composites. Evolutions of microstructure for the developed AlMg/SiC composites was investigated by optical microscopy.